Filling the Void: The Role of Adult Siblings Caring for a Brother or Sister With Severe Mental Illness - Gabriele Kitzmüller; Lena Wiklund Gustin; Anne Martha Kalhovde (SAGE Publishing, 2023)
Little is known about the role of adult siblings' caregiver role within the context of mental illness. Therefore, our purpose was to explore how siblings narrate their experiences of being the main caregivers of a brother or sister with severe mental illness and how they cooperate with their ill sibling and their family of origin. We used a narrative hermeneutic approach and performed a secondary analysis of two interviews of siblings derived from a study of peoples' experiences of hearing voices. The findings illuminate the participants' multifaceted roles and how differently siblings might deal with the multiple challenges of caring for an ill sibling. The mediating role between their ill sibling and their family of origin to reestablish the broken family bonds was a significant aspect. Nurses' awareness of the important and multidimensional role of caregiving siblings can improve the provision of family support and promote involvement of siblings in the treatment of an ill family member.